New Images of Old Age towards the Further Aging Population Process - Iwański, Rafał (Studia Oeconomica Posnaniensia, 2017)
The aim of this paper is to examine the adequacy of current mainstream criteria, and dimensions of old age studies in the view of the possible future further aging population process. The populations of highly developed countries are in the middle of aging processes. Demographic predictions indicate the significant growth of senior citizens among western societies in next decades. At the same time fertility rates will fall and average life expectancy will rise. The median age in Poland in 2014 was 39.4, while the prognosis for 2050 anticipates value of 52 [GUS 2014, 2015]. The population ageing process in Polish society will be one of the fastest among current EU members states [Mossakowska, Więcek i Błędowski 2012]. The social, demographical, economic and technological changes lead us to the urgent need to open up a discussion on how to redefine old age in very basic dimensions.